Mice with NOP2/sun RNA methyltransferase 5 deficiency die before reaching puberty due to fatal kidney damage - Hongya Zhang; Xiaohui Li; Jing Bai; Cong Zhang (Renal Failure)
Background NOP2/Sun RNA methyltransferase 5 (NSUN5) is an RNA methyltransferase that has a broad distribution and plays critical roles in various biological processes. However, our knowledge of the biological functions of NSUN5 in mammals is very limited. Therefore, in this study, we investigate the role of NSUN5 in mice.Methods In the present research, we built a mouse model (Nsun5-/-) using the CRISPR/Cas9 system to investigated the specific role of NSUN5.Results We observed that Nsun5-/- mice had a reduced body weight compared to wild-type mice. Additionally, their survival rate gradually decreased to 20% after postnatal day (PD) 21. Further examination revealed the Nsun5-/- mice had multiple organ damage, with the most severe damage occurring in the kidneys. Moreover, we observed glycogen deposition and fibrosis, along with a notable shorting of the primary foot processes of glomeruli in Nsun5-/- kidneys. Furthermore, we found that the kidneys of Nsun5-/- mice showed increased expression of the apoptotic signal Caspase-3 and accumulated stronger DNA damage at PD 21.Conclusions In our study, we found that mice lacking NSUN5 died before puberty due to kidney fatal damage caused by DNA damage and cell apoptosis. These results suggest that NSUN5 plays a vital role in preventing the accumulation of DNA damage and cell apoptosis in the kidney.